DELINIASI SEBARAN NILAI PERMEABILITAS SEKUNDER UNTUK MEMPERKIRAKAN POTENSI ALIRAN AIRTANAH PADA TAMBANG BAWAH TANAH KUBANG CICAU PT. ANEKA TAMBANG TBK LOKASI RAMP DOWN, PONGKOR, KABUPATEN BOGOR, JAWA BARAT - Dhony Indrawan; Henarno Pudjihardjo; Wahju Krisna Hidajat; Yosep Purnama (Program Studi Teknik Geologi, Fakultas Teknik, Universitas Diponegoro, 2014)
Tunnel development on UBPE Pongkor is an ongoing and continuous work to take existing gold reserves in gold mining Pongkor site. One of the development work is making the access to the location of ore mining process to be carried out, one of the existing ore is the Kubang Cicau location . However, the process of mining and development plans on the location of the tunnel ramp down Kubang Cicau disorder caused the groundwater flow resulting in ponding of water is high enough on the location of the south ramp down Kubang Cicau so need to do the research include hydrogeological studies on secondary permeability values that exist in study siteThe research carried out by the method of observation on the location of the ramp down Kubang Cicau include calculation of fracture parameters for the calculation of the value of secondary permeability Snow equation ( 1968 ) as well as observations of the condition of the ramp down Kubang Cicau especially the condition of water flowing through the tunnel wall. Secondary permeability values at study sites will affect the flow of groundwater potential zones and take effect on groundwater flow patterns.The study was conducted at the location of the ramp down and ramp up Kubang Cicau at an elevation of 450-500 meters above sea level . Based on the analysis it was found that the flow of groundwater in the study site predominantly influenced by secondary permeability is influenced by the media cracks in the rocks . In the research area known secondary permeability values at locations greater than the ramp down ramp up locations , with most of the secondary permeability value of 3.17 10-2 m/s were found in the location of the point is in south ramp down Kubang Cicau mine . Based on the distribution of secondary permeability values can be concluded that the potential for groundwater flow is in the southern part of the ramp down and ramp down groundwater flow toward the south .